The Life History of Khalid ibn al-Walid: From Enemy to Companion of the Prophet - Astuti, Alika Fidiyah; Putri, Fanida Amelia; Hidayah, Anggun Naya Salma (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
Khalid ibn al-Walid was one of the most influential military figures in Islamic history, famously known as the “Sword of Allah.” He came from the Banu Makhzum clan of the Quraysh tribe, which had a strong military tradition. Before embracing Islam, Khalid was a prominent commander of the Quraysh forces opposing the Muslims, including in the Battle of Uhud. However, after the Treaty of Hudaybiyyah, he began to reflect on the message of Islam and eventually converted in 629 CE.This study aims to examine Khalid ibn al-Walid’s social and military background, his transformation from an adversary into a leading commander of the Muslim army, and his contributions in several significant battles such as Mu’tah, the conquest of Mecca, Yamamah, and Yarmouk. The research uses a qualitative method with a historical approach and narrative analysis of both primary and secondary sources.The findings reveal that Khalid’s strategic brilliance, bravery, and loyalty played a vital role in strengthening the Muslim community and expanding Islamic territory—during both the time of the Prophet Muhammad (peace be upon him) and the caliphates of Abu Bakr and Umar ibn al-Khattab. Khalid’s life story reflects the power of divine guidance, steadfast faith, and exemplary courage and dedication to the religion.